Direct sum of π-projective semimodules - Altaee, Muna M. T.; Alhossaini, Asaad. A. M. (Iraqi Journal of Science, 2022)
Let A, and N are a semiring ,and a left A- semimodule, respectively. In this work we will discuss two cases: The direct summand of π-projective semi module is π-projective, while the direct sum of two π-projective semimodules in general is not π-projective . The details of the proof will be given.We will give a condition under which the direct sum of two π-projective semi modules is π-projective, as well as we also set conditions under which π-projective semi modules are projective.